Pengembangan Media Jelita Sebagai Sarana Eksplorasi Peristiwa Ikonik Umar bin Khattab pada Siswa Sekolah Dasar - nisa nurpasa (Atthiflah: Journal of Early Childhood Islamic Education, 2026)
This study aims to develop and test the feasibility and effectiveness of JELITA (Jelajah Lini Masa Kalender Hijriyah) media as a historical exploration tool capable of enhancing cognitive understanding and the internalization of moral values (ibrah) of the Khulafaur Rasyidin, specifically regarding Umar bin Khattab for 6th-grade elementary students. The method used is Research and Development (R&D) applying the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research and trials were conducted on 22 6th-grade students at SDN Baginda 1. Validation results from material and media experts indicated that the JELITA media falls into the "Highly Feasible" (Sangat Layak) category. Furthermore, the implementation results showed a significant improvement in cognitive understanding, marked by a drastic increase in the students' average scores from the pre-test to the post-test stage. Some students even experienced a dramatic score increase from 20 to a perfect 100. In addition to its cognitive impact, JELITA media also proved effective in facilitating students' social awareness through the internalization of Umar bin Khattab's exemplary values, and it received highly positive responses from students for being interactive and not boring.